INSAN KAMIL DALAM PERSPEKTIF MUHAMMAD IQBAL - Rusdin Rusdin (Rausyan Fikr: Jurnal Ilmu Studi Ushuluddin dan Filsafat, 2016)
Every being has individuality or self. Degree elevation on every being in nature depending on the level of development of each individuality. The criteria for determining the quality of every being is how far he can live up to himself effectively. Individuality is the distinguishing mark in the concept of Khudi or Iqbal ego. Iqbal's philosophy about Khudi ends on his thoughts about the insan kamil, the ideal man. Insan kamil is the highest level that can be achieved not by way of meditation, but with an original creative work, which is lawful overwhelmed by love or ishq, firmness self or faqr, courage and tolerance. Achieve this through three phases: obedience to God, self-control and the caliphate of God.